Nanocrystalline cellulose, an environmental friendly nanoparticle for pharmaceutical application – a quick study - Song, Yee Kai; Chew, Irene Mei Leng; Choong, Thomas Shean Yaw; Tan, Khang Wei (EDP Sciences, 2016)
Nanocrystalline cellulose (NCC) is probably the most abundant nano material can be found in nature. It offers not only substantial environmental advantage due to its intrinsic biocompatibility and biodegradability, but also outstanding aspect ratio, tension modulus, bioavailability and permeability. NCC can be isolated from low value biomass through a well-developed acid hydrolysis method, and the structure can be readily manipulated during extraction to obtain desirable size distribution, surface charge and degree of crystallinity. Erratic absorption of drug has been a major issue for years until the emergence of nanoparticle adopted as smart vehicle for drug delivery. However, due to inevitably severe toxicity and the side effect from ordinary nanoparticle, the exploration of green nanoparticles are catching escalating attention is now in urge. Microcrystalline cellulose (MCC) has long been an option, nevertheless, due to their relatively low surface charge compared to total volume, drug release in a control manner was hardly satisfied. It is suggested that the above limitation can be overcome by nanocrystalline cellulose. This article discusses and explores their potential in cosmetic, personal care and pharmaceutical application, and the recent development in term of preparation and characteristic.